Effect of pgsE expression on the molecular weight of poly(γ-glutamic acid) in fermentative production - Fujita, Ken-Ichi; Tomiyama, Takashi; Inoi, Takahiro; Nishiyama, Takashi; Sato, Eriko; Horibe, Hideo; Takahashi, Ryosuke; Kitamura, Shinichi; Yamaguchi, Yoshihiro; Ogita, Akira; Tanaka, Toshio (Polymer journal, 2021)
Poly(γ-glutamic acid) (PGA) is a biopolymer produced by Bacillus spp. via the γ-amide linkages of d - and/or l -glutamate. Although high-molecular-weight (HMW) PGA possesses many attractive properties, such as flocculating, wound healing, and immune-stimulating effects, no studies have reported factors useful for increasing the molecular weight of PGA during microbial production. PgsB, PgsC, and PgsA are the minimum protein sets required for PGA production in B. subtilis , and PgsE improves PGA productivity. Analysis by size-exclusion chromatography combined with multiangle laser light scattering revealed that the molecular weight of PGA was M w = 2,900,000 g mol −1 and predominantly M w = 47,000 g mol −1 in preparations derived from B. subtilis cells with and without pgsE , respectively. PgsE may be required to increase the molecular weight of PGA. Poly(γ-glutamic acid) (PGA) is a biopolymer produced by Bacillus spp. via the γ-amide linkages of d - and/or l -glutamate. PgsB, PgsC, and PgsA are the minimum protein set required for PGA production in B. subtilis , and PgsE improves PGA productivity. Analysis by size-exclusion chromatography combined with multiangle laser light scattering revealed that the molecular weight of PGA was M w = 2,900,000 g mol −1 or predominantly M w = 47,000 g mol −1 in preparations derived from B. subtilis cells with or without pgsE , respectively. PgsE may be required to increase the apparent molecular weight of PGA.